The unbearable weight of message or on the translation of oral sources in oral history research - Wiktoria Kudela-Świątek (Wrocławski Rocznik Historii Mówionej, 2012)
This text has come to life from the belief that there is a need of reflection on the issue of translation of oral history accounts as a part of researcher’s technique. In spite of the importance of the quality of narrative sources translations, this subject is often disregarded by researchers dealing with oral history not only in Poland but also abroad. So far only the British oral history researchers have been interested in this subject. Therefore in my own observations I focused on the questions of genre classification of oral history narrations, existence of cultural community between the interviewee and the researcher, including the question of whether the researcher knows the language of the researched group or people, I also considered social and cultural background in translations of biographic narrations. I find these matters crucial for proper understanding and translation of biographic narrations content to the reader’s language.